PREDICTING POLITENESS STRATEGIES IN ENGLISH CONVERSATION - Hoebe, Susanne E. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Brown and Levinson (1987) put forward the formula ‘Wx = D (S, H) + P (H, S) + Rx’ to calculate the weightiness of face-threatening acts. I tested this formula on English conversations in three of Tom Stoppard’s radio plays, using both qualitative and quantitative analyzes. The results of this study show that the formula does predict politeness strategies used by speakers in interactions, but more so in longer scenes than in shorter ones. Analysis of deviating cases suggests that such factors as the number of utterances per interaction, personal style, background or class, impoliteness or rudeness, overpoliteness, situational factors, metalanguage and effective writing by the playwright may explain why speakers in particular cases do not use the politeness strategy that they are expected to utilize in accordance with the social relation (D), the power relation (P), and the absolute ranking of the imposition (R) found in the interaction. The existence of lower-level goals in longer conversations also influences a speaker’s choice of strategy. I will introduce two coefficients that can be applied to the formula, a variable factor of Instrumentality (I) and a constant factor of Personal Style (C), leading to an adaptation of the formula: ‘Wx = (D (S, H) + P (H, S) + Rx) x I x C’.